The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/nau.22307
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pubovisceral muscle avulsion in a general gynecology cohort: A computed tomography (CT) study

Abstract: The prevalence of pubovisceral muscle avulsion using CT scanning in a general gynecology cohort is 6.4%. Thinning of the pubovisceral muscle occurs with parity and protracted labor and is more prominent on the left portion of the muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Our results of the levator symphysis gap with 19.8 mm for the right side and 21.3 mm for the left side were well comparable to the results by Derpapas et al, reporting 21.2 mm for the right side and 22.5 mm for the left side ( P = 0.17, P = 0.29) . However, the mean values in our study were higher compared to Singh et al using a 3D‐MRI‐model, reporting 17.4 mm for the right side and 18.0 mm for the left side ( P = 0.03, P < 0.05) …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our results of the levator symphysis gap with 19.8 mm for the right side and 21.3 mm for the left side were well comparable to the results by Derpapas et al, reporting 21.2 mm for the right side and 22.5 mm for the left side ( P = 0.17, P = 0.29) . However, the mean values in our study were higher compared to Singh et al using a 3D‐MRI‐model, reporting 17.4 mm for the right side and 18.0 mm for the left side ( P = 0.03, P < 0.05) …”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, Zhuang et al defined the measurement on a 3D model as the distance from the middle of the inferior symphysis to the nearest aspect of the pubovisceral muscles on each side . On the other hand, Singh et al and Derpapas et al measured each side of the levator symphysis gap as the distance from the anterior aspect of the levator ani muscle to the closest point of the pubic symphysis on transversal plane . In our study, we measured the width from the anterior‐lateral part of the puborectal muscle to the most lateral part of the pubic symphysis still visible on the same transversal slice, similar to Derpapas et al on axial CT scans, as there was no muscle avulsion …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Other studies have found the risk of urinary incontinence decreased, a highly counterintuitive finding . The prevalence of “avulsion” varies significantly, ranging from 6% to 50%, depending on the imaging technique used …”
Section: Introductionmentioning
confidence: 99%